Pengaruh Harga, Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Pelanggan Omah Kopi Rupa Palembang - adriana, delsa putri; Lestari, Retno Budi (Universitas Multi Data Palembang, 2023)
The purpose of this study was to analyze the effect of price, product quality and service quality on customer satisfaction at Omah Kopi Rupa Palembang. This study used a data collection method using a questionnaire and using an interval scale with a total sample of 276 respondents. This type of research uses quantitative research. The data collection technique uses a sampling technique with a probability sampling technique with the SPSS version 26 statistical test tool. Based on the results of the study, the variables of price, product quality and service quality have a significant effect on customer satisfaction at Omah Kopi Rupa Palembang.